Implementation of a Novel Hydraulic Hybrid Powertrain in a Sports Utility Vehicle. Issue 15 (2015) - Sprengel, Michael; Bleazard, Tyler; Haria, Hiral; Ivantysynova, Monika
Abstract: Hydraulic hybrid transmissions offer an efficient and high performance alternative to electric hybrid transmission in on-road vehicles. One of the principle benefits of hydraulic over electric hybrids is the higher power density offered by their energy storage media. This enables hydraulic hybrids to capture virtually all of the available kinetic energy from braking. In contrast electric hybrids are often forced to dissipate part of this energy through friction brakes due to the lower power density inherent in their energy storage media. To date various hydraulic hybrid architectures have been investigated and put into production. However as is typically true there always exists room for improvement. This paper details the integration of a novel blended hydraulic hybrid transmission with improved performance and efficiency into a demonstration vehicle. Also included is a discussion of various unique control strategies which were designed for this powertrain as well as a discussion of initial measurement.